Juharmanik: Portraits of Women in Mamaca Text Edits and Hermeneutical Studies - Agustina Dewi Setyari; Akhmad Sofyan; Dewi Angelina; Panakajaya Hidayatulah (MOZAIK HUMANIORA, 2022)
This study describes the text, transliteration, translation of the text, editing of the text, and analysis of the contents of the text with the study of hermeneutics. The theory used in this study is the theory of philology. The text editing process and Gadamer's hermeneutic theory are used to reveal the meaning of Juharmanik's story. In this research using qualitative methods in the form of data inventory, data processing, and presentation of the results of data analysis. The results of the hermeneutical analysis are based on four concepts, namely 1) bildung to understand the text through the history of the formation of the text, 2) census communis is a view of the true and general goodness, 3) judgment is used to classify specific things on the basis of a view of the universal , and 4) tastes, namely subjective attitudes related to various tastes. The concept is an analytical process used to find meaning in the text. The meaning contained in the Juharmanik text is that every child must be devoted to his parents, be honest, not slander, be able to control himself and his passions, be patient in facing life's trials and accept the provisions that have been given by God.